2015
DOI: 10.1016/j.jelectrocard.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The availability of prior ECGs improves paramedic accuracy in recognizing ST-segment elevation myocardial infarction

Abstract: Abstract:Introduction: Early and accurate identification of ST-Elevation Myocardial Infarction (STEMI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Recording of pre-hospital ECG and notification of PCI center result in a substantial reduction in reperfusion time which in turn leads to survival benefit [13][14][15]. O'Donnell et al [16] reported that the availability of prior ECG recordings improved paramedic accuracy in recognizing ST-elevation pattern and diagnosing STEMI. In the present study it was found that only 38.4% of physician-led ambulances and 60% of paramedic-led ambulances transmitted ECG recording to a PCI center (p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Recording of pre-hospital ECG and notification of PCI center result in a substantial reduction in reperfusion time which in turn leads to survival benefit [13][14][15]. O'Donnell et al [16] reported that the availability of prior ECG recordings improved paramedic accuracy in recognizing ST-elevation pattern and diagnosing STEMI. In the present study it was found that only 38.4% of physician-led ambulances and 60% of paramedic-led ambulances transmitted ECG recording to a PCI center (p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy for improving computerized STEMI detection would be incorporating prior ECG findings into computerized algorithms since serial ECGs can significantly increase the sensitivity for a STEMI diagnosis [6,16,17]. Prior studies show that serial or continuous ECGs improve the diagnostic accuracy for STEMI since a single static “snap-shot” 12-lead ECG may miss dynamic ischemic changes.…”
Section: Discussionmentioning
confidence: 99%
“…12,22,24 The addition of paramedic or physician review of the ECG can improve accuracy and allows inclusion of the patient's symptoms and medical history, and prior ECGs when available, in the decision process. 25,26 Interestingly, on review of the ECGs, 18% of those initially classified as FP had an ischemic ST pattern suggestive of a possible acute coronary occlusion. From a systems perspective, this can be considered an appropriate trigger for CCL activation.…”
Section: Discussionmentioning
confidence: 99%